Comparative analysis and evaluation methods of depreciation of fixed assets for the purposes of accounting and taxation - T. V. Voronchenko; N. V. Rybkina (Путеводитель предпринимателя)
The article presents the results of a study of the methods ofdepreciation of fixed assets for the purposes ofaccounting and taxation, a comparative analysis of application of different methods and estimation of their influence on taxable profit business structures and the current tax on profit.